Efeito da cor circundante e da espessura da amostra no potencial de ajuste de cor de um compósito monocromático - Barros, Mariana Silva (2022)
Propose: This study evaluated the effect of surrounded shade and specimens` thickness on the color adjustment potential of a monochromatic composite. Methodology: The composite Vittra APS Unique was surrounded (dual specimens) or not (single specimens) by a control composite (shade A1D, A2D, or A3D). Single specimens of control composite were also confectioned. Opacity and whiteness index for dentistry (WID) were calculated for single specimens. Color differences between the single (ΔEab*SIMPLE)/ dual specimens (ΔEab*DUAL) and the controls were calculated. CAP was calculated based on the ratio between ΔEab* SIMPLE and ΔEab* DUAL. Results: The tested composite presented lower opacity (53 to 62% vs. 80 to 93%) and the higher WID (≈ 42 vs. 18 to 32) than controls. Irrespective of the specimens’ thickness (1.0/ 1.5 mm), the lowest values of ΔEab* SIMPLE (11.1/ 10.8) and ΔEab*DUAL (7.2/ 6.1) were observed using the surrounding shade A1D. The shade A3 yielded higher ΔEab*SIMPLE (16.4/ 17.1) and ΔEab* DUAL (11.3/ 12.3) than the A2D (ΔEab*SIMPLE = 13.4/ 14.6; and ΔEab* DUAL = 9.7/ 10.3). The specimen`s thickness significantly affected the CAP (0.35 and 0.44 for 1.0 and 1.5 mm, respectively) only for shade A1D, which had the highest CAP values. The shade A3D resulted in higher CAP values (0.31) than A2D (0.27) when 1.0-mm thick specimens were used, but similar values were observed for 1.5 thick specimens (≈ 0.29). Conclusion: Both surrounding shade and specimen thickness can affect the CAP of a monochromatic resin composite, and the highest values were observed for shade A1 and 1.0-mm thick specimens.